Characteristics of otologic disease among patients with primary ciliary dyskinesia - ERDEM ERALP, ELA (My University, 2023)
Importance Otologic disease is common among people with primary ciliary dyskinesia (PCD), yet little is known about its spectrum and severity. Objective To characterize otologic disease among participants with PCD using data from the Ear-Nose-Throat Prospective International Cohort. Design, Setting, and Participants This cross-sectional analysis of baseline cohort data from February 2020 through July 2022 included participants from 12 specialized centers in 10 countries. Children and adults with PCD diagnoses; routine ear, nose, and throat examinations; and completed symptom questionnaires at the same visit or within 2 weeks were prospectively included. Exposures Potential risk factors associated with increased risk of ear disease. Main Outcomes and Measures The prevalence and characteristics of patient-reported otologic symptoms and findings from otologic examinations, including potential factors associated with increased risk of ear inflammation and hearing impairment. Results A total of 397 individuals were eligible to participate in this study (median [range] age, 15.2 [0.2-72.4] years; 186 (47%) female). Of the included participants, 204 (51%) reported ear pain, 110 (28%) reported ear discharge, and 183 (46%) reported hearing problems. Adults reported ear pain and hearing problems more frequently when compared with children. Otitis media with effusion—usually bilateral—was the most common otoscopic finding among 121 of 384 (32%) participants. Retracted tympanic membrane and tympanic sclerosis were more commonly seen among adults. Tympanometry was performed for 216 participants and showed pathologic type B results for 114 (53%). Audiometry was performed for 273 participants and showed hearing impairment in at least 1 ear, most commonly mild. Season of visit was the strongest risk factor for problems associated with ear inflammation (autumn vs spring: odds ratio, 2.40; 95% CI, 1.51-3.81) and age 30 years and older for hearing impairment (41-50 years vs ≤10 years: odds ratio, 3.33; 95% CI, 1.12-9.91). Conclusion and Relevance In this cross-sectional study, many people with PCD experienced ear problems, yet frequency varied, highlighting disease expression differences and possible clinical phenotypes. Understanding differences in otologic disease expression and progression during lifetime may inform clinical decisions about follow-up and medical care. Multidisciplinary PCD management should be recommended, including regular otologic assessments for all ages, even without specific complaints.